PENGARUH ORIENTATION MARKET DAN PRODUCT INNOVATION TERHADAP PERFORMANCE MARKETING PADA PERUSAHAAN PT. NOVAPHARIN GRESIK - Dewi, Shinta (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
This aims of this study is to determine the effect of orientation marketing and product innovation on performance marketing in PT. Novapharin Gresik. This type of research is survey research and this study uses a quantitative approach. Sampling is done by using a purposive sampling method that is with certain considerations so that the number of samples obtained is 100 people. Data was collected using a questionnaire that had been tested for validity and reliability and carried out classical assumption tests. The data analysis technique used is multiple linear regression. This analysis model is used to determine the effect of independent variables on the dependent variable. Empirically The results of the study show that there is a simultaneous influence of the Orientation Marketing and Product Innovation variables on Performance Marketing and partially influence, that Orientation Marketing has a positive and significant effect on Performance Marketing and Product Innovation has a positive and significant effect on Performance Marketing. Keywords: Orientation Marketing, Product Innovation, and Marketing Performance